GORE® CARDIOFORM ASD occluder thrombus in a patient of rheumatoid arthritis occurred three days after deployment - Nakagawa, Naomi; Shigemitsu, Yusuke; Okamoto, Kengo (International journal of cardiology congenital heart disease, 2025)
A 67-year-old female patient with rheumatoid arthritis that was well suppressed by medications except for steroids had catheter closure of the secundum atrial septal defect (ASD). After the administration of aspirin and intravenous heparin, a 32-mm of GORE® CARDIOFORM ASD occluder was successfully deployed. On postprocedural day 3, transthoracic echocardiography showed mobile echogenic mass of 9 mm on the right side of the device. Intravenous heparin 10 IU/kg/hr was administrated continuously, and clopidogrel was added. On the following day, the mobile mass was not visible. Even though the occurrence rate of device thrombus is not high, device thrombosis can become a major complication of device closure of ASD because it may cause systemic and/or pulmonary embolism. Administration of dual antiplatelet therapy or other anticoagulant therapy should be considered if the patients have a higher risk of thrombosis.